Financial remoteness and the net external position - Martin Schmitz (European Central Bank (ECB), 2011)
This paper shows that, controlling for standard determinants of net external positions, financially-remote countries exhibit more positive net external positions. This finding is found to be stronger for less advanced countries, hinting at external funding problems for more remote countries. Being located near financially very open countries, being in currency unions with creditor countries, or being highly integrated through financial and trade linkages with a `core' country facilitates net external borrowing. Consequently, evidence is found for an important role of geographic and bilateral factors for a country's net external wealth.
Keywords: F21; F34; F41; 330; Cross-Border Investment; distance; net foreign assets; proximity